Prognostic role of tripartite motif containing 24 in various human solid malignant neoplasms: An updated meta-analysis and systematic review. Issue 51 (23rd December 2021) - Xue, Yifeng; Ge, Wei; Shi, Wenhua; Huang, Weihua; Wang, Rong
Abstract: Background: Currently, clinical studies of tripartite motif containing 24 (TRIM24) on human solid malignant neoplasms were developing, but the prognosis value of TRIM24 continues to be controversial. The aim of our study is to explore the prognostic effect of TRIM24 in various human solid malignant neoplasms. Methods: We performed a comprehensive research for eligible studies which evaluated the prognostic roles of TRIM24 in cancer patients based on PubMed, Embase, Web of Science, and China National Knowledge Infrastructure. The hazard ratios (HRs) with 95% confidence intervals (CIs) for various malignances were extracted from eligible studies. Results: A total of 13 studies with 1909 patients were enrolled in this analysis. Combined analyses showed that high expression of TRIM24 significantly predicted poorer overall survival both in univariate analysis (HR = 1.61, 95% CI 1.21–2.15, P = .001) and multivariate analysis (HR = 2.19, 95% CI 1.10–4.38, P = .026). In stratified analyses, high TRIM24 expression level predicted even worse overall survival in hormone-related cancers (HR = 1.92, 95% CI 1.28–2.86, P = .001). Although, expression of TRIM24 failed to show a significant relation with progression-free survival/disease-free survival/recurrence-free survival (HR = 1.42, 95% CI 0.93–2.16, P = .106), high expression predicted significant worse progression-free survival/disease-free survival/recurrence-free survival in hormone-related cancer (HR = 1.71, 95% CI 1.12–2.59, P = .013). Conclusion: TRIM24 could serve as a new biomarker for patients with solid malignancies and could be a potential therapeutic target for patients especially for patients with hormone-related malignancies. Abstract : Supplemental Digital Content is available in the text